2002
DOI: 10.1046/j.1540-8167.2002.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Atrioventricular Parasympathetic Innervation in Humans

Abstract: For the first time in humans, an epicardial fat pad was identified from which parasympathetic nerve fibers selectively innervate the AV node but not the sinoatrial node. Nerves in this fat pad also innervate the surrounding right atrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 1 publication
3
53
1
Order By: Relevance
“…38 The AV-node is highly innervated by parasympathetic nerve fibers where Na v 1.8 is expressed. [39][40][41] Recognition of disease mechanisms overlap between the AF and AV-nodal re-entry tachycardia, and the fact that AVNRT may be the triggering factor for AF has been reported in several studies. [42][43][44][45] Consistent with this notion, several of our paroxysmal AF patients with the rare variants have AVNRT (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The AV-node is highly innervated by parasympathetic nerve fibers where Na v 1.8 is expressed. [39][40][41] Recognition of disease mechanisms overlap between the AF and AV-nodal re-entry tachycardia, and the fact that AVNRT may be the triggering factor for AF has been reported in several studies. [42][43][44][45] Consistent with this notion, several of our paroxysmal AF patients with the rare variants have AVNRT (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…46 Changes in autonomic tone, also known as sympathovagal imbalance, are important triggers in some forms of paroxysmal AF and also in the generation and maintenance of persistent AF. [41][42][43] With the expression of Na v 1.8 channels in vagal fibers and their absence in sympathetic fibers, it is possible that the observed effects on Na v 1.8 function of the different variants alters the sympathovagal balance. 19,20,22 We were able to examine 3 families for cosegregation of SCN10A variants identified in the respective probands (Table 1), but none of the family members diagnosed with AF carried the variant of the proband.…”
Section: Discussionmentioning
confidence: 99%
“…21 Numerous studies have observed multiple major and small GPs in the atria of mammalian hearts. 19,[22][23][24] These GPs modulate the interaction and balance between the extrinsic and intrinsic autonomic nervous system and contain efferent cholinergic and adrenergic neurons which influence the atrial myocardium, 25 in terms of action potential duration, AERP, and conduction velocity. In many animal studies, autonomic denervation exhibited short-term efficacy.…”
Section: Changes In the Electrophysiological Characteristics In The Tmentioning
confidence: 99%
“…It contains abundant parasympathetic fibers that affect AV node conduction. 6,7 After proof of concept in humans, we and others developed a technique for chronic endocardial 8,9 and epicardial 10 neurostimulation of the RIGP for ventricular rate control during atrial fibrillation (AF) in dogs. Of note, the negative dromotropic effect during endocardial HFES could be maintained throughout the entire neurostimulation period of 2 years.…”
mentioning
confidence: 99%